Alquran Values-Integrated Physics Modul: The Effect on Students’ Problem Solving Skill and Spiritual Attitude in Physics - Herni Yuniarti Suhendi; Diah Mulhayatiah; Nur Komalasari; Ryan Ardiansyah; Rahayu Kariadinata (JIPF (Jurnal Ilmu Pendidikan Fisika), 2022)
Along with the development of technology, education today must create a quality young generation (students). This quality is not only intellectual, but in terms of the spiritual attitude and skills produced, one of the most needed is problem solving skill. This study aims to determine the effect of implementation physics module integrated with Quran values on problem solving abilities and spiritual attitudes of students in physics learning. The used method in this study is experiment with Non Equivalent Control Group Design. The sample consisted of 2 class X MIA selected through a purposive sampling technique. The results showed that there was a significant influence of the use of physics module integrated with Quran on the problem solving ability and spiritual attitudes of students in physics learning. The integrated physics module with Qur’an values is able to train problem solving skills that are needed by students in the process of thinking solutions to a problem in real life in physics concept and also able to grow spiritual attitudes as an effort to fulfill the first core competence, namely spiritual competence.